ADSORPSI KESADAHAN (Ca) MENGGUNAKAN ADSORBEN BERBASIS SEKAM PADI - A.S. Dwi Saptati Nur Hidayati, Juliananda, Bambang Ismuyanto (Universitas Sumatera Utara, 2016)
This study reports adsorption of hardness (Ca) onto rice husk-basedadsorben. Characterization of rice husk-based adsorbent was identified by FTIR. Experiments were carried aout with several parametersvariations such as adsorption time (30-180 minutes) and the initial hardness (Ca) concentration (164.8 to 329.6) mg/L. Furthermore, initial study to evaluate the feasibility of adsorbent application was doneusing Langmuir and Freundlichtest. The results showed that hardness (Ca)removalup to 35.98% at a concentration of Na2SO41 M and adsorption time 150 minutes. The adsorption data obtained data were fitted well to Langmuir isotherm model with adsorption capacity of rice husk-based adsorbent was found to be 18.52 mg/g.